2019
DOI: 10.1038/s41467-019-10189-x
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes causes marked inhibition of mitochondrial metabolism in pancreatic β-cells

Abstract: Diabetes is a global health problem caused primarily by the inability of pancreatic β-cells to secrete adequate levels of insulin. The molecular mechanisms underlying the progressive failure of β-cells to respond to glucose in type-2 diabetes remain unresolved. Using a combination of transcriptomics and proteomics, we find significant dysregulation of major metabolic pathways in islets of diabetic βV59M mice, a non-obese, eulipidaemic diabetes model. Multiple genes/proteins involved in glycolysis/gluconeogenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

21
249
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 255 publications
(274 citation statements)
references
References 58 publications
21
249
2
2
Order By: Relevance
“…Thus, our experimental approach better mimics the environment that b-cells from overfed, obese, or pre-diabetic patients may be subjected to, thereby avoiding more extreme mTORC1-mediated responses such as glucotoxicity-induced ER stress or glucose starvation-induced autophagy. In a recent study, INS-1 cells exposed to 25 mM glucose for 48 h had increased anaplerosis and flux through the pentose phosphate pathway (Haythorne et al, 2019), which are consistent with our findings. In contrast, oxidative metabolism was reduced and pyruvate metabolism was blocked in INS-1 cells exposed to 25 mM glucose for 48 h, which is the opposite result from what we obtained using 11 mM glucose and shorter exposure.…”
Section: Discussionsupporting
confidence: 93%
“…Thus, our experimental approach better mimics the environment that b-cells from overfed, obese, or pre-diabetic patients may be subjected to, thereby avoiding more extreme mTORC1-mediated responses such as glucotoxicity-induced ER stress or glucose starvation-induced autophagy. In a recent study, INS-1 cells exposed to 25 mM glucose for 48 h had increased anaplerosis and flux through the pentose phosphate pathway (Haythorne et al, 2019), which are consistent with our findings. In contrast, oxidative metabolism was reduced and pyruvate metabolism was blocked in INS-1 cells exposed to 25 mM glucose for 48 h, which is the opposite result from what we obtained using 11 mM glucose and shorter exposure.…”
Section: Discussionsupporting
confidence: 93%
“…However, triggering mechanisms of mitochondrial dysfunction and/ or inflammation in diabetes are still ill-understood. Chronic hyperglycaemia 46 was recently suggested to start a vicious cycle of progressive deterioration of β-cells by impairing insulin secretion and mitochondria. However, our study clearly demonstrated that non-diabetic subjects developed diabetes within 4 years when they showed high levels AhRL and/or MIS in serum (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have demonstrated that mitochondrial dysfunction contributes to the deterioration of beta cell function and plays a role in the development of T2D [3,14,[51][52][53]. Deletion of Drp1 from primary mouse beta cells resulted in glucose intolerant mice, with impaired GSIS and abnormal mitochondrial morphology associated with lower expression of MFN1, MFN2 and OPA1 [54,55].…”
Section: Discussionmentioning
confidence: 99%